Perlindungan Hukum Terhadap Nasabah Pengguna ATM - Hattu , Yakoba Yuliana (Jurnal Ilmu Hukum Kyadiren, 2024)
This research discusses the legal protection for clients who use automated teller machines (ATMs) at the Bank BNI Biak Branch and the bank’s responsibility for losses incurred by customers during transactions. The data collection techniques utilized qualitative descriptive research with empirical and normative data analysis. The research findings indicate that legal protection for clients aligns with Consumer Protection Law Number 8 of 1999. The bank provides compensation for losses in two ways: mistakes and unlawful acts. The bank is responsible for reimbursing customer losses. Efforts to prevent legal issues are undertaken by implementing restorative justice, which includes establishing banking mediation institutions, standardizing customer complaint procedures, enhancing product information transparency, and improving consumer education. Civil disputes can be resolved through civil law processes by filing a lawsuit with the appropriate court.